2019
DOI: 10.18291/njwls.v9i2.114803
|View full text |Cite
|
Sign up to set email alerts
|

ICT Intentions and Digital Abilities of Future Labor Market Entrants in Finland

Abstract: Daily lives of citizens in current societies have changed with the spread of digital technologies, online services, and digital communication. Alongside this, the information and communication technology (ICT) labor force is expected to grow massively over the next years, requiring increased number of applicants for digital education and sufficient digital skills from every labor market entrant. This study examines the digital abilities of Finnish upper secondary school students (N = 3206) and the students' in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
1
Order By: Relevance
“…Four studies (#13, #32, #86, #102) found that technology skills bring such benefits, albeit in ways that are differentiated by gender. Two of these studies measured digital skills using performance tests: study #13 found that greater digital skills are associated with interest and competence in using computers; study #32 found that ‘the likelihood of students choosing the ICT field increased significantly along with greater competence in both medium-related skills and programming skills’ (Kaarakainen, 2019: 120). In study #86, like most other studies based on a self-reported measure of digital skills, the association found between greater computer skills and ICT-related career aspirations is stronger for girls than boys.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (#13, #32, #86, #102) found that technology skills bring such benefits, albeit in ways that are differentiated by gender. Two of these studies measured digital skills using performance tests: study #13 found that greater digital skills are associated with interest and competence in using computers; study #32 found that ‘the likelihood of students choosing the ICT field increased significantly along with greater competence in both medium-related skills and programming skills’ (Kaarakainen, 2019: 120). In study #86, like most other studies based on a self-reported measure of digital skills, the association found between greater computer skills and ICT-related career aspirations is stronger for girls than boys.…”
Section: Resultsmentioning
confidence: 99%
“…The most common shortcoming was to include items that were too vague or general. Examples of this are items such as: "accessing information with a computer" (Areepattamannil & Khine, 2017), "maintaining social relationships [online]" (Kaarakainen, 2019) or "interpreting and representing information, such as using ICT to synthesize, summarize, compare and contrast information from multiple sources" (Lau & Yuen, 2015). Sometimes more than one "sin" was committed.…”
Section: Presence Of Best and Problematic Practices In The Skills Measurement Literaturementioning
confidence: 99%
“…The second best practice guideline ("Avoid device-, platform-or activity-specific items to make sure that skills items measure transferrable skills and can continue to be used over time") is applied on a more widespread basis (Alkan & Meinck, 2016;Kaarakainen, 2019;Porat, Blau, & Barak, 2018), although some studies still include device-specific items, for example, mobile phone-related items, here and there (Areepattamannil & Khine, 2017;Lee, 2018;Rodríguezde-Dios, Igartua, & González-Vázquez, 2016). Similarly, the third best practice guideline ("Different items should be designed to capture (functional) digital skills and (critical) digital knowledge") is rarely violated, in the sense that very few studies combine functional and critical elements in the same item.…”
Section: Presence Of Best and Problematic Practices In The Skills Measurement Literaturementioning
confidence: 99%
“…El PA, en particular, se considera una habilidad muy importante, la cual está ganando cada vez más terreno en la educación primaria y secundaria de los países en desarrollo dinámico (Zsakó & Szlávi, 2012); su incidencia en las perspectivas de desarrollo de la educación, ha impulsado que algunos currículos estén promoviendo la enseñanza de la programación, el pensamiento algorítmico y la solución de problemas de manera integrada en sus planes de estudio (Kaarakainen, 2019) y ha sido declarado como meta primordial de gran parte de los sistemas educativos modernos como Australia, China, Finlandia, Japón, Corea y Reino Unido, entre otros (Vidal et al, 2015). En este orden de ideas, el PA puede aportar al desarrollo de habilidades para la RP, abriendo oportunidades didácticas que permitan una planificación de estrategias orientadas al favorecimiento de habilidades de pensamiento en los estudiantes frente al contexto problemático del mundo actual.…”
Section: Introductionunclassified